Emergence of sensory structures in the developing epidermis in sepia officinalis and other coleoid cephalopods. Issue 13 (8th April 2014) - Buresi, Auxane; Croll, Roger P.; Tiozzo, Stefano; Bonnaud, Laure; Baratte, Sébastien
ABSTRACT Embryonic cuttlefish can first respond to a variety of sensory stimuli during early development in the egg capsule. To examine the neural basis of this ability, we investigated the emergence of sensory structures within the developing epidermis. We show that the skin facing the outer environment (not the skin lining the mantle cavity, for example) is derived from embryonic domains expressing the Sepia officinalis ortholog of pax3/7, a gene involved in epidermis specification in vertebrates. On the head, they are confined to discrete brachial regions referred to as "arm pillars" that expand and cover Sof‐pax3/7‐negative head ectodermal tissues. As revealed by the expression of the S. officinalis ortholog of elav1, an early marker of neural differentiation, the olfactory organs first differentiate at about stage 16 within Sof‐pax3/7‐negative ectodermal regions before they are covered by the definitive Sof‐pax3/7‐positive outer epithelium. In contrast, the eight mechanosensory lateral lines running over the head surface and the numerous other putative sensory cells in the epidermis, differentiate in the Sof‐pax3/7‐positive tissues at stages ∼24–25, after they have extended over the entire outer surfaces of the head and arms. Locations and morphologies of the various sensory cells in the olfactory organs and skin were examined using antibodies against acetylated tubulin during the development of S. officinalis and were compared with those in hatchlings of two other cephalopod species. The early differentiation of olfactory structures and the peculiar development of the epidermis with its sensory cells provide new perspectives for comparisons of developmental processes among molluscs. J. Comp. Neurol. 522:3004–3019, 2014. © 2014 Wiley Periodicals, Inc.